FRI0498 A Quantitative Videocapillaroscopic Study about the Relationship of Avascular Areas with the Clinical Characteristics and Disease Severity in Patients with Systemic Sclerosis. (10th June 2014) - De Angelis, R.; Salaffi, F.; Di Donato, E.; Muti, S.; Grassi, W.
Abstract : Background: Several studies have been carried out in systemic sclerosis (SSc) in order to correlate the microvascular damage with the clinical features and/or organ involvement, most of them by using the qualitative or semiquantitative assessment of the morphological abnormalities forming the so-called "scleroderma pattern". The reduction in the number of capillaries is a predominant feature, being the direct expression of the progressive and widespread endothelial damage. Quantitative studies about the scleroderma pattern are currently scarce and none addressed the relationship between the avascular areas (absence of loops at nailfold that extends over more than 500 microns) with the clinical characteristics of the SSc. Objectives: To evaluate in a series of SSc patients the association between the extent of the avascular areas with both clinical features and disease severity. Methods: Fifty-four patients (47 women and 7 men, mean age 59.5 years, median disease duration 13.0 years) were consecutively enrolled and underwent nailfold videocapillaroscopy. For each patient, a total of 32 images were collected (4 images were representative of the entire nailfold per each finger). All images were classified according to the following patterns: normal, non-specific, scleroderma pattern (with or without avascular areas). The videocapillaroscopic patterns were correlated with such features as sex, age, disease duration, blood chemistry data. The disease severity was measured by the score of Medsger which gives a judgment about 9 indicators (general, peripheral vascular, skin, tendons, muscle, gastrointestinal tract, lung, kidney, heart). Results: A total of 1728 images were analyzed. Patients were divided into 4 groups, on the basis of the extent of the avascular areas. In group 1 (6 patients, 11.1%) the extent was less than 25%, in group 2 (5 patients, 9.2%) the extent was between 25-50%, in group 3 (16 patients, 29.7%) between 50-75%, in group 4 (27 patients, 50%) the extent was more than 75%. Group 1 and group 2 showed no significant relationship with any of the variables considered. Patients in group 3 had a significant correlation with the presence of digital ulcers (p=0.007). The group 4 (involving more than 75% of the entire nailfold microcirculation) showed a significant correlation with the indicator of vascular disease severity (p=0.002), history of digital ulcers (p=0.045) and the presence of active digital ulcers (p≤0.0001). No association was found between the extent of avascular areas and/or disease duration, as other indicators of disease severity. Conclusions: The correlation observed between the peripheral vascular disease severity (Raynaud's pnenomenon, pitting scars, digital ulcers, gangrene) and the presence of "active" digital ulcers and/or history of digital ulcers with the extent of the avascular areas represents a relevant data, confirming the hypothesis of a strong link between the fingertip blood perfusion and the integrity of the nailfold microvasculature. The lack of correlation between the extent of the avascular areas with the disease's duration supports the concept that the severity of microangiopathy is not characteristic of the late stages of the SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4412